Parallel‐in‐time‐and‐space electromagnetic transient simulation of multi‐terminal DC grids with device‐level switch modelling - Tianshi Cheng (Wiley, 2022)
Abstract The electromagnetic transient (EMT) simulation of multi‐terminal DC (MTDC) grids requires a detailed device‐level modular multilevel converter (MMC) model, which can have thousands of state variables and complex internal structures. The fast device‐level insulated gate bipolar transistor (IGBT) transient requires a very small time‐step, making the computational overhead prohibitive. Based on the analysis of the parallel‐in‐time (PiT) implementation of detailed modelled MMCs, this paper proposes a task‐based hybrid PiT algorithm to achieve high parallel efficiency and speed‐up of MMC with device‐level modelling. Moreover, a transmission line model(TLM)‐based parallel‐in‐time‐and‐space (PiT+PiS) method is proposed to connect PiT grids to conventional or other PiT grids and exploit the maximum parallelism. Simulation results show greater than 30× speed‐up and 60% parallel efficiency on a 48 cores computer for the hybrid PiT method in a 201‐level three‐phase MMC test case, and 20× speed‐up in the transient simulation of CIGRÉ B4 DC grid test system for the PiT+PiS method.